Nanowire formation for single electron transistor using SEM based Electron Beam Lithography (EBL) technique: Positive tone vs negative tone e-beam resist - Mohammad Nuzaihan, Md Nor; Uda, Hashim; Nur Hamidah, Abdul Halim; Bajuri, S. N M (Nano Science and Technology Institute, 2009)
Link to publisher's homepage at http://www.nsti.org/Nanotech2006/